Strategi Pengembangan Peternakan Itik Petelur Di Kabupaten Lebong - Gandi, Kardinal Alsepto; Putranto, Heri Dwi; Brata, Bieng; Nurmeiliasari , Nurmeiliasari; Badarina, Irma (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
The strategy for developing laying ducks in Lebong Regency aims to explore potential, formulate strategies and overcome existing problems, so that they can interpret plans and programs from the Government of Lebong Regency as contained in the Strategic Plan-DPP 2016-2021 to realize self-sufficiency in food and products with high added value based on local resources for food sovereignty and farmer welfare, from 25 respondents who were chosen purposively (purposive sampling) consisting of breeders and stakeholders. The data processing method uses a strategic management concept approach with qualitative analysis and quantitative analysis (internal and external factors) to formulate three stages of strategy, namely the input stage uses the IFE matrix (Internal Factor Evaluation) and the EFE matrix (External Factor Evaluation), the integration stage is carried out with the IE matrix. (Internal-External), SWOT matrix (Strength, Weakness, Opportunities, Threats), the decision-making stage uses QSPM (Quantitative Strategy Planning Matrix). From the analysis results IFE 3.0571 and EFE 3.1216 combined in the I-E Matrix are in cell I position, which means that the development of laying duck farms in Lebong Regency is in strong internal conditions and the response to external factors is relatively high, a strategy that can be applied to laying duck farms in the District Lebong, namely the Growth and Build strategy (grow and develop) either through an intensive strategy or an integration strategy, based on the SWOT line quadrant graph shows a positive position both the X axis = 6.40 (opportunities) and the Y axis = 8.12 (strength) strategy Appropriate marketing is aggressive. From the results of the QSPM with a score of 4.9761, the priority strategy for developing laying duck farms in Lebong Regency that can be implemented is increasing production capacity, increasing livestock capacity by increasing the number of laying duck populations and increasing the ability of human resources in the field of animal husbandry, especially laying ducks, with that an aggressive strategy can be implemented. carried out so that market demand for duck eggs can be fulfilled.   Keywords: Development strategy, laying Ducks, Lebong District